Killer whales in the Gulf of Mexico and North Atlantic off the Southeastern United States - Kevin P. Barry; Keith D. Mullin; Katherine Maze-Foley; Lynsey A. Wilcox Talbot; Patricia E. Rosel; Melissa S. Soldevilla; Laura Aichinger Dias; M. Rafael Ramírez-León; Jenny A. Litz (Frontiers in Marine Science, 2024)
Killer whales occur in the Gulf of Mexico (GoMex) and the North Atlantic, including off the southeastern United States (SEUS). Data from cetacean surveys during 1990 – 2021 and other sources were combined to assess killer whale biology, including spatial and temporal distribution, social structure, genetics, morphology, acoustics, and predatory behavior. GoMex records occurred predominantly in oceanic waters (>200 m) during spring and summer. SEUS records occurred primarily in winter and spring off the North Carolina region along the shelf-edge and deeper waters, and off the east coast of Florida. Photo-identification analysis of GoMex killer whales resulted in 49 individuals sighted up to seven times with sighting histories up to 26 years, and social analysis provided evidence of long-term relationships up to 16 years. The GoMex genetic samples revealed two mtDNA haplotypes, one of which does not match any outside the GoMex. Most GoMex whales had wide non-faint saddle patches and many had cookiecutter shark scars while no scars were noted on SEUS whales. Three groups recorded in the GoMex made few calls, but a group harassing sperm whales produced many. Cetaceans and tuna are known prey in the GoMex and SEUS, respectively. Directed studies of killer whales in the GoMex areas would be difficult to implement as this species is very rare. It is therefore important to pursue ongoing efforts to collect behavioral, acoustic and any biological samples that will contribute to improve our understanding of the biology and ecology of killer whales in tropical and subtropical regions.

Anisotropic dispersal by the Asian longhorned beetle (Anoplophora glabripennis): quantifying spatial risk and eradication effort with limited biological data - R. Talbot Trotter; Eugene Pepper; Kevin Davis; Ryan Vazquez (Biological Invasions, 2019)

Towards a TDP-43-Based Biomarker for ALS and FTLD - Emily Feneberg; Elizabeth Gray; Olaf Ansorge; Kevin Talbot; Martin R. Turner (Molecular Neurobiology, 2018)

Optimizing Photo-Encapsulation Viability of Heart Valve Cell Types in 3D Printable Composite Hydrogels - Laura Hockaday Kang; Patrick A. Armstrong; Lauren Julia Lee; Bin Duan; Kevin Heeyong Kang; Jonathan Talbot Butcher (Annals of Biomedical Engineering, 2017)

Characterisation of novel point mutations in the survival motor neuron gene SMN , in three patients with SMA - Leigh Skordis; Matthew Dunckley; Lydia Burglen; Louise Campbell; Kevin Talbot; Shobna Patel; Judith Melki; Kay Davies; Victor Dubowitz; Francesco Muntoni (Human Genetics, 2001)